The art of using the needle - Holroyd, Ina E. (My University, 1897)
Introduction: “The needle, though it be but small and slender, Yet it is both a maker and a mender; A grave reformer of old rents decay’d, Stops holes and seams and desperate cuts display’d.” The needle is a tiny instrument which belongs almost exclusively to woman, how essential then that she should be able to use it well and that she get all the art out of it which it is capable of yielding. That woman should sew seems to be a necessity; she has sewed through countless ages and probably will continue to do so as long as she exists. “’Till the world be quite dissolved and past, So long at least the needle’s use shall last.” Of the first efforts along this line we read in Genesis where Mother Eve sewed fig leaves together for covering.
Citation: Holroyd, Ina E. The art of using the needle. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Needle; Sewing; History; Art; Theses; Manuscripts (documents)